2013
DOI: 10.1051/epjconf/20134501085
|View full text |Cite
|
Sign up to set email alerts
|

Computational aeroacoustics of human phonation

Abstract: The current paper presents a CFD model of flow past vibrating vocal folds coupled to an acoustic solver, which calculates the sound sources from the flow field in a hybrid approach. The CFD model is based on the numerical solution of 3D Navier-Stokes equations on a time-dependent domain, solved by cell-centered finite volume method. To capture the fine turbulent scales important for the acoustic source calculations, the equations are discretized and solved on large computational meshes up to 3.2M elements. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Yet, it has been demonstrated that flow changes from laminar to transitional or turbulent only at high airflow rates, such as that seen during physical activity. 61,62,68 Furthermore, it has been demonstrated that for moderate airflow rates, simulated nasal resistances and CFD models results with or without turbulence components are very similar. 1,2 Finally, the settings for the CFD analysis, namely the air temperature and humidity, the density and viscosity of the airflow, and the negative pressure assumed at the nasopharynx, are approximations of the normal breathing conditions.…”
Section: Limitations Of Cfd Analysismentioning
confidence: 89%
See 1 more Smart Citation
“…Yet, it has been demonstrated that flow changes from laminar to transitional or turbulent only at high airflow rates, such as that seen during physical activity. 61,62,68 Furthermore, it has been demonstrated that for moderate airflow rates, simulated nasal resistances and CFD models results with or without turbulence components are very similar. 1,2 Finally, the settings for the CFD analysis, namely the air temperature and humidity, the density and viscosity of the airflow, and the negative pressure assumed at the nasopharynx, are approximations of the normal breathing conditions.…”
Section: Limitations Of Cfd Analysismentioning
confidence: 89%
“…The airflow is assumed to be laminar according to data that have demonstrated nasal airflow to be almost exclusively laminar during resting breathing, only changing to transitional or turbulent at high flow rates. 1,61,62 Using particle image velocimetry and flow visualization, Doorly et al demonstrated that airflow is laminar at quiet breathing flow rates. 40 Furthermore, good agreement was found between CFD simulations using laminar airflow and in vitro measurements at airflow rates up to 250 mL/second.…”
mentioning
confidence: 99%
“…ANSYS Fluent™ uses the finite volume method in cell-centered approach to numerically solve the discretized Navier-Stokes equations. Since the flow velocities through the nasal passage during low to moderate breathing rate usually have a Mach number ≪ 0.2, (27) the conservation of mass and momentum governing equations for laminar, incompressible steady state flow reduces to u=0, ρ(u)u=p+μ2u, where u=u(x,y,z) is the velocity vector, ρ = 1.204 kg/m 3 is fluid density, μ = 1.825 × 10 ‒5 kg/m ‒ s is dynamic viscosity, and ρ is pressure. The thermal energy equation for heat transfer is defined as ρcp(u)T=k2T, where T = T ( x,y,z ) is temperature, k = 0.0268 W/m-K is thermal conductivity, c p = 1005.9 J/kg-K is specific heat of air.…”
Section: Methodsmentioning
confidence: 99%
“…ANSYS Fluent uses the finite volume method to numerically solve the discretized Navier–Stokes equations. Because the flow velocities through the nasal passage during low-to-moderate breathing rate usually have a Mach number , 45 the conservation of mass and momentum governing equations for laminar, incompressible steady-state flow reduces to …”
Section: Methodsmentioning
confidence: 99%